EVIDENCE-BASED CASE REPORT (EBCR) PIJAT BAYI UNTUK BAYI USIA 3-6 BULAN (Politeknik Kesehatan Kemenkes Bandung, 2022)
The prenatal period until toddlerhood is referred as the golden period because of the growth and development of brain cells. Early stimulation can affect the infants growth and development through various pathways. One of the early stimulation is through gentle touches such as baby massage and baby gym. A study shows that one third of children in developing countries do not achieve optimal growth and development. Based on 2016 Ministry of Health data, 27.7% of children under five were stunted thus can affect the cognitive and socio-emotional development of children. Research conducted in the Jakarta area shows that the prevalence of developmental delays in children aged 3-60 months were around 10%. Stimulation that the baby receives directly affects the brain development and increase in the baby's weight. Diego et al in 2005 showed infant massage effectively increase premature babies body weight with an average of 31-49% and was followed by an increase in head circumference and height. This EBCR aims to determine the effect of massage on infants aged 3-6 months. The method used is Evidence Based Case Report using 3 databases, namely: Google Scholar, Garuda Portal and Pubmed with the year published 2019. The inclusion criteria used were full text articles, English / Indonesian, there are four journals that can be used in accordance with the objectives of the Evidance Based Case Report. The results shows that stimulation in the form of baby massage and baby gym can improve the quality and quantity of baby sleeping periode, and build affection between mother and baby. Keywords: Infant massage, Infants aged 3-6 months, and sleep quality.